Career Perception from the Perspective of the Students of Sports Sciences Faculty: A Metaphor Study - Cihan ULUN (ümit doğan üstün, 2023)
The aim of this study is to examine the career perceptions of sports science students by metaphors. The study was carried out in a phenomenological pattern, one of the qualitative research types. Research data was obtained from a total of 192 students studying at Gazi University Faculty of Sports Sciences in the 2022-2023 academic year, saying "Career is like ... because..." It was obtained by completing the expressions. When the frequencies of the metaphors are examined, the metaphors with at least two repetitions are "life (20), stairs (10), money (10), road (8), success (6), obligation (6), development (5), key (4), iceberg (4), flower (4), mountain (4), future (4), light (4), identity (4), tree (3), gold (3), child (3), sword (3), status (3), step (2), diamond (2), house (2), everest (2), sapling (2), need (2), door (2), luxury (2), mission (2), reward (2), water (2), climbing (2) and star (2)". When the metaphor findings were examined, 7 categories consisting of 192 valid metaphors were identified. When the metaphors expressed by the participants and their justifications were examined, it was seen that the majority of them were used in a positive. When the categories created in the study are examined, it is seen that the categories are "Development process (f=48, 25%), Status (f=35, 18.22), Quality of Life (f=34, 17.70%), Difficulty (f=30, 15.62%), Need/ It was seen that it was shaped under the headings "Necessity (f=30, 15.52%), Risk (f=16, 8.33%) and Purchasing Power (f=4, 2.11%)". As a result of the study, it was seen that the participants perceived the concept of career as a development process for their working lives, an effective situation on their quality of life, a social status, a need/requirement in terms of sustaining human life, a process full of difficulties, risky and closely related to the purchasing power of individuals.